Screening Zizhyphus germ plasm against powdery mildew - N.D. JAMBHALE, T. PRADEEP* and (Indian Phytopathology, 2002)
Of the 82 ber accessions belonging to Zizhyphus mauritiana and one accession to Z. rugosa evaluated for resistance to powdery mildew under natural epiphytotic conditions, four genotypes viz., Darakhi-l, Darakhi-Z, Seedless and Z. rugosa exhibited immune reaction in leaves and fruits while Guli and Villaiti, for fruits only. Leaf reaction of bud grafted seedlings of the 56 genotypes including immune ones under polyhouse conditions revealed susceptibility of all the genotypes except seedless. This was further confirmed by detached leaf culture technique in the laboratory and the immunity of seedless leaves could be attributed to some inbuilt resistance mechanism. Results of the different screening experiments suggested that the ber genotypes exhibited differential response to powdery mildew in young and mature leaves as well as fruits.